On inequalities of some integral transforms - ALBAYRAK, DURMUŞ; ERDOĞAN, EZGİ; UÇAR, FARUK (My University, 2021)
In this presentation, we obtain integral inequalities which involves some integral operators defined on Banach space of absolutely p-integrable functions by using well-known inequalities. Applying these inequalities, we give also some illustrative examples. Keywords: Integral inequalities; Bounded operators; Integral transforms.
Keywords: Integral inequalities; Bounded operators; Integral transforms